Failure Analysis of Bolted Connection Subjected to Torsional Loadings - Sai, Susharrman; SUBRAMANIYAN, S KANNA (Research Progress in Mechanical and Manufacturing Engineering, 2024)
In mechanical engineering, the integrity of bolted connections under stress is critical. This study focuses on the failure mechanisms of these connections  under  torsional   loading.   The   objective   was   to simulate the mechanical performance of a particular failed bolted joint under varying torsional loads. Using SolidWorks for 3D modelling and ANSYS for finite element analysis, the research methodically evaluates the performance of the failed bolted joint under various torsional loads ranging from 2.5 to 20 Nm. Key findings reveal excessive stress distribution patterns and specific failure points. The study concludes with design recommendations for an optimized bolt joint which ensures that stress and strain values remain well below the material's failure benchmarks.